A Revolution in Mathematics?: What Really Happened a Century Ago and Why It Matters Today - Quinn, Frank (The Best Writing on Mathematics 2013, 2014)
The physical sciences all went through ‘‘revolutions”: wrenching transitions in which methods changed radically and became much more powerful. It is not widely realized, but there was a similar transition in mathematics between about 1890 and 1930. The first section briefly describes the changes that took place and why they qualify as a “revolution,” and the second section describes turmoil and resistance to the changes at the time. The mathematical event was different from those in science, however. In science, most of the older material was wrong and discarded, whereas old mathematics needed precision upgrades but was mostly correct. The